PENGARUH PEMBERIAN DUAL TASK TRAINING TERHADAP PENURUAN RISIKO JATUH PADA LANSIA - Candraningtyas, Puteri Nabila; Asita Rohmah Muntanawasitoh; Dita Mirawati; Dea Linia Romadhoni (Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Background: A fall is defined as an accidental loss of balance that causes a person unprepared. The risk of falling in the elderly is related to a decrease in balance, namely the elderly cannot control balance in their posture during dynamic or static positions and gait disorders. Poor balance control is affected by several physiological factors that interfere with independence and contribute to the risk of falls and injuries. Dual task training is an exercise where the subject is given instructions to do 2 tasks at the same time. Interventions that combine motor and cognitive tasks are carried out simultaneously which allows for increased recognition of the disorder that occurs and accelerates the process of restoring body functions. Objective: To determine the effect of dual task training on reducing the risk of falls in the elderly. Methods: This type of research is a quantitative research, quasi-experimental Quasy Experimental Pre-Post Test With Control Group Design with a total of 26 subjects. The research instrument used questionnaires, interviews, and measurement of falling risk with TUGT. The dual task training intervention in the elderly was carried out 3 times a week in 4 weeks. Results: The results of this study showed that there was a significant effect of dual task training on reducing the risk of falling in the elderly with a significance value of p = 0.008 (p<0.05). Conclusion: There was an effect on the subjects after being given an intervention in the form of dual task training. Keywords: Fall Risk; Dual Task Training; Time Up and Go Test